VARIÁVEIS PSICOSSOCIAIS DE MÃES PRIMÍPARAS E SUAS IMPLICAÇÕES NO DESENVOLVIMENTO DE SEUS FILHOS - BERBERT-FERREIRA, MÁRCIA (2019)
It presents a study that aimed to evaluate and describe the correlation between maternal psychosocial variables: schooling, exclusive income, self-esteem, perception of satisfaction with their relationship as a couple and signs of possible postpartum depression and the development of children in their first 42 months of life. For this purpose, 82 primiparous mothers and their 82 single offspring, under their care or of first-degree relatives, without financial ties, were selected from families living in Uberlândia, State of Minas Gerais. This is a quantitative, cross-sectional study with a non-probabilistic sample, which used, as a maternal evaluation tool: a sociodemographic questionnaire, Rosenberg Self-esteem Scale, Factorial Satisfaction Scale in Couple Relationship and Edinburgh Postpartum Depression Scale. To assess children up to 42 months, the Bayley III Scales were used to quantify cognitive, language, motor, socioemotional, and adaptive behavior skills. For data analysis, the software BioEstat, version 5.3, and the Spearman correlation test, with significance of 5%, α ≤ 0.05 were used. The results showed that exclusive maternal income had a positive and statistically significant correlation with cognitive ability (rs=0.2339, p=0.0344), expressive language (rs=0.3523, p=0.0012), fine motor (rs=0.2183, p=0.0487) and the adaptive behavior (rs=0.2731, p=0.0130). Maternal schooling presented a positive and statistically significant correlation with cognitive abilities (rs=0.2850, p=0.0094), fine motor (rs=0.3239, p=0.0030) and adaptive behavior (rs=0.2236, p=0.0433). Maternal schooling also presented statistically significant positive correlation with the child development in cognitive (rs=0.2850, p=0.0094), fine motor (rs=0.3239, p=0.0030) and adaptive behavior (rs=0.2236; p=0.0433) abilities. The variables self-esteem and maternal perception of satisfaction with their relationship and couple did not present correlations with any of the developmental abilities evaluated for Bayley III Scales; and the signs of postpartum depression presented an inverse and statistically significant correlation, only with the cognitive ability of the children evaluated (rs=-0.2550, p=0.0207). The results of this research indicate the need for new actors to be able to give full attention to these families and maximize the potential of these children in order to promote health and prevent injuries.